Parliamentary Diplomacy of Taiwan in Comparative Perspective : Against Isolation and Under-representation - Šabič, Zlatko; Huang, David W. F. (Book collections on Project MUSE., 2021)
Through a comparative perspective, and using evidence from the relations of the Legislative Yuan in Taiwan with the US Congress and the European Parliament, this book assesses both the potentials and the constraints of parliamentary diplomacy for Taiwan.